Proposal of an algorithm for the management of rectally inserted foreign bodies: a surgical single-center experience with review of the literature - Fritz, Stefan; Killguss, Hansjörg; Schaudt, André; Sommer, Christof M.; Richter, Götz M.; Belle, Sebastian; Reißfelder, Christoph; Loff, Steffan; Köninger, Jörg (Langenbeck's archives of surgery, 2022)
Retained rectal foreign bodies (RFBs) are uncommon clinical findings. Although the management of RFBs is rarely reported in the literature, clinicians regularly face this issue. To date, there is no standardized management of RFBs. The aim of the present study was to evaluate our own data and subsequently develop a treatment algorithm.
Gesehen am 25.09.2023